IMF Staff papers : Volume 11 No. 2. (IMF Staff Papers; IMF Staff Papers ;, 1964)
This paper outlines the extent of the IMF with its present policies and practices or with some modification of those policies and practices that is capable of dealing satisfactorily with certain problems of international liquidity. Liquidity that is conditional in any of these senses may be somewhat less prized by the country possessing it than would be an equivalent amount of unconditional liquidity; but the imposition of such conditions may be for the general advantage of the international community, and may make countries having surpluses in their balances of payments readier to provide, or to facilitate the provision of, additional liquidity. An increased supply of the type of liquidity of which the use is subject to policy conditions will have somewhat different results. Although it will probably increase the amount and the financing of external deficits, even this is not certain. The various types of liquidity are to some extent substitutes for each other.